Study of J/ψ azimuthal anisotropy at forward rapidity in Pb-Pb collisions at √sNN=5.02 TeV - Acharya, S.; Torales-Acosta, F.T.; Adamovã, D.; Adler, A.; Adolfsson, J.; Aggarwal, M.M.; Aglieri Rinella, G.A.; Agnello, M.; Agrawal, N.; Ahammed, Z.; Ahn, S.U.; Aiola, S.; et al. (Springer Verlag, 2019)
The second (v2) and third (v3) flow harmonic coefficients of J/ψ mesons are measured at forward rapidity (2.5 < y < 4.0) in Pb-Pb collisions at sNN = 5.02 TeV with the ALICE detector at the LHC. Results are obtained with the scalar product method and reported as a function of transverse momentum, pT, for various collision centralities. A positive value of J/ψ v3 is observed with 3.7σ significance. The measurements, compared to those of prompt D0 mesons and charged particles at mid-rapidity, indicate an ordering with vn(J/ψ) < vn(D0) < vn(h±) (n = 2, 3) at low and intermediate pT up to 6 GeV/c and a convergence with v2(J/ψ) ≈ v2(D0) ≈ v2(h±) at high pT above 6–8 GeV/c. In semi-central collisions (5–40% and 10–50% centrality intervals) at intermediate pT between 2 and 6 GeV/c, the ratio v3/v2 of J/ψ mesons is found to be significantly lower (4.6σ) with respect to that of charged particles. In addition, the comparison to the prompt D0-meson ratio in the same pT interval suggests an ordering similar to that of the v2 and v3 coefficients. The J/ψ v2 coefficient is further studied using the Event Shape Engineering technique. The obtained results are found to be compatible with the expected variations of the eccentricity of the initial-state geometry.
Keywords: Physics; Rapidity; Meson; Particle physics; Analytical Chemistry (journal); Large Hadron Collider; Chemistry; https://purl.org/pe-repo/ocde/ford#1.03.03